Relationship between deviatoric stress distribution and failure characteristics of roadway considering axial stress - Hongtao LIU; Zijun HAN; Zihan CHEN; Linfeng GUO; Jialu LIANG; Zhou HAN; Qinyu LIU; Yue JI (Meitan xuebao)
Through theoretical analysis, a three-dimensional model of the full-plane strain problem considering the influence of the axial stress of the roadway is established. The implicit analytical solution of the second invariant deviatoric stress J2 of the roadway surrounding rock under the three-dimensional stress field is derived. The distribution and morphological evolution of J2 under different horizontal lateral pressure and axial lateral pressure stress environments in the elastic state and plastic state of the roadway surrounding rock are analyzed. Based on the Kastner solution method, the implicit solution of the plastic zone boundary of roadway surrounding rock under three-dimensional stress field is obtained, and the distribution characteristics of plastic zone of roadway surrounding rock under different stress conditions are studied by mathematical and numerical analysis methods. The corresponding relationship between the second invariant deviator stress J2 and the plastic zone shape of surrounding rock is established, and the deformation and failure mechanism of surrounding rock is revealed. Taking the return airway of 31205 working face in Cuncaota No.2 Mine as the engineering background, the distribution characteristics of J2 and plastic zone of roadway surrounding rock under superimposed mining are studied, the characteristics of asymmetric deformation and failure are quantified, the interaction relationship between support resistance and J2 is sought, and the stability control technology of superimposed mining roadway is proposed. The results show that: When the axial lateral pressure value is fixed and the horizontal lateral pressure value is changed, the morphological distribution characteristics of J2 and plastic zone show the evolution process of “circular-elliptical-butterfly-like”. When the horizontal lateral pressure value is fixed and the axial lateral pressure value is changed, the shape of J2 and plastic zone remains unchanged. The change of axial stress has little effect on the shape of plastic zone, but has a great influence on the size of plastic zone. The greater the concentration of surrounding rock J2, the greater the degree of deformation and failure of surrounding rock. The distribution of J2 determines the failure mode of plastic zone to a certain extent. The 31205 return airway is in a high deviatoric stress J2 environment under the influence of superimposed mining, and the stress distribution characteristics of rotating to the side of the goaf are formed, resulting in the formation of asymmetric large deformation and failure of the roadway. The increase of support resistance has limited effect on the decrease of deviatoric stress J2 of roadway surrounding rock, and it is impossible to completely control the stability of roadway surrounding rock only by bolt (cable). Based on the above research, the combined control technology of advanced strong support + bolt (cable) support system is proposed, and the field application effect is good.